Better Late Than Never: Effects of Late ACA Medicaid Expansions for Parents on Family Health-Related Financial Well-Being - Caitlin McPherran Lombardi PhD; Lindsey Rose Bullinger PhD; Maithreyi Gopalan PhD (SAGE Publishing, 2022)
Public health insurance eligibility for low-income adults has improved adult economic well-being. But whether parental public health insurance eligibility has spillover effects on children's health insurance coverage and family health-related financial well-being is less understood. We use the 2016 to 2020 National Survey of Children's Health (NSCH) to estimate the effects of Medicaid expansions through the Affordable Care Act (ACA) for parents on child health insurance coverage, parents' employment decisions due to child health, and family health-related financial well-being. We compare children in low-income families in states that expanded Medicaid for parents after 2015 to states that never expanded in a difference-in-differences framework. We find that these expansions were associated with increases in children's public health insurance coverage by 5.5 percentage points and reductions in private coverage by 5 percentage points. We additionally find that parents were less likely to avoid changing jobs for health insurance reasons and children's medical expenses were less likely to exceed $1000. We find no evidence that the expansions affected children's dual coverage and uninsurance. Our estimates are robust to falsification and sensitivity analyzes. Our findings also suggest that benefits on children's medical expenses are concentrated in the families with the greatest financial need.